An applied course in real options valuation - Shockley, Richard L. (Richard Lester) (Thomson Higher Education, 2007)
APPLIED COURSE IN REAL OPTIONS VALUATION, offers an excellent guide to option pricing in today's fast paced business world. This innovative text not only provides the theories of option pricing but includes real-world examples and situations.